Dramatic decrease of flood frequency in the Mekong Delta due to river-bed mining and dyke construction - Park, Edward; Huu Loc Ho; Dung Duc Tran; Yang, Xiankun; Alcantara, Enner [UNESP]; Merino, Eder; Vu Hai Son (Elsevier B.V., 2020)
Here we present a proof of concept evaluation of the impacts of riverbed-mining on river-wetland connectivity by analyzing the temporal trends of the flood frequencies in the Vietnamese Mekong Delta (VMD), while accounting for the effect of dyke constructions. We focus on the Long Xuyen Quadrangle (LXQ), which is significant in terms of biodiversity and economic contribution to the VMD as it is one of the most important food baskets of Southeast Asia that depends on seasonal flooding. Our results indicate that the flood frequency in LXQ has decreased significantly over the past 20 years (1995-2015). Time-series analyses of water level data at Chau Doc, Tan Chau, and Can Tho stations confirmed that the overall descending trend is statistically significant (p-value < 0.001 and tau similar to 0.1). However, the river discharge at Kratie showed no significant trend (p-value = 0.98) over the same period. This indicates that the flood frequency is associated with the lowering of the riverbed (incision) other than climatic factors. The connectivity analysis also revealed a remarkable drop in the inundation duration after early 2000, which corresponds to the previous observations of the shifting shoreline of the VMD from construction to shrinking. Finally, regression and principal component analyses underpinned the strong causality between the riverbed-mining and the decreased seasonal flooding patterns in LXQ, while accounting for the effect of the dyke system over the last decades (R-2 = 0.75). This study offers compelling evidences on the relationship between sand-mining in the river and the disrupted flood regimes in VMD. The reduction in water and sediments that is necessary for sustaining current rates of agricultural production in the long term would endanger the livelihoods of millions of VMD inhabitants. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Floods; Flood frequency; Sand mining; Dykes; Mekong River; Vietnam